Analisis Strategi Pemasaran untuk Meningkatkan Penjualan Produk Asuransi Syariah - Lintang Dwiyana; Nuri Aslami (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
Insurance is an arrangement whereby the insurer binds the insured by receiving a premium, to compensate for the loss, damage, or loss of projected profits that the company may incur as a result of an uncertain event. Regarding the economy, insurance refers to an economic agreement that eliminates or reduces negative impacts in the future due to different possibilities (Asriyadi, 2019: 50). Sharia insurance is one of the institutions that provide services in the service sector, emerging in the midst of society, most of which are still do not understand about sharia insurance and use it. This causes people to be reluctant to use insurance services by labeling sharia. Marketing strategy is essentially a comprehensive, integrated and integrated plan in the field of marketing that provides guidance on the activities to be carried out to achieve the marketing goals of an entrepreneur. Entrepreneurship is a form of activity of people who are able to face challenges and take advantage of existing opportunities, while realizing a vision. Sharia insurance products cover 4,444 different products, namely insurance products with 4,444 savings items and 4,444 non-saving insurance products. Non-savings insurance products cover 4,444 individuals' health, personal accident and personal Al-Khairat. AlKhairat is for those who intend to replace the heirs if the participant experiences death during the agreement period (Ramadhani, 2015). To improve their products, many insurance companies are innovating by introducing new features, such as health insurance. Facilitate public access to insurance, especially for health insurance. Keywords: Insurance, Marketing Strategy, Sharia Insurance Products